Determination of Employee Performance: Work Environment and Leadership Style : (Case Study at PT. MPIW Jakarta) - Roni , Faizal; Handoko, Melyani; Parancika, Rd Bily; Aris, Mohammad; Ardi, Yahya Mara; Syabrinildi (Journal of Management and Informatics, 2025)
In today’s dynamic industrial environment, optimizing employee performance has become a strategic imperative for organizational sustainability. Among the factors that significantly influence workforce outcomes, the physical work environment and leadership style stand out as pivotal drivers. This study explores how these two variables affect employee performance within PT. MPIW, a prominent manufacturing firm in Jakarta. Employing a quantitative approach, data were obtained through structured questionnaires from 50 purposively selected respondents working in logistics, production, and purchasing divisions. Using IBM SPSS Statistics 21, the analysis revealed compelling insights. The work environment demonstrated a strong and positive influence on employee performance (t = 11.883, p < 0.001), affirming that factors such as spatial adequacy, safety, and interpersonal dynamics play a crucial role in enhancing productivity. Surprisingly, leadership style exerted a negative and statistically significant effect (t = -3.880, p < 0.001), suggesting that the prevailing authoritarian tendencies may undermine employee morale and engagement. The joint influence of both variables was also found to be significant (F = 86.518, p < 0.001), underscoring their combined relevance in shaping performance outcomes. This study contributes a critical perspective on organizational behavior in the manufacturing sector by integrating environmental and managerial dimensions into a unified analytical model. The findings underscore the need for adaptive, participatory leadership approaches and strategic enhancement of workplace conditions to drive sustainable performance improvements.